(untitled) (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
The development of efficient nano‑based drug delivery systems remains a critical strategy for improving the stability, bioavailability, and therapeutic performance of plant‑derived bioactive compounds. In this study, methanolic root extract of Imperata cylindrica was synthesized, characterized, and nanoencapsulated using chitosan as a biodegradable and biocompatible polymeric carrier, with the objective of enhancing its suitability for wound‑healing and hemostatic drug delivery applications. Qualitative and quantitative phytochemical analyses revealed the presence of alkaloids (5.4%), tannins (5.7%), flavonoids (10.3%), saponins (2.25%), and terpenoids (43.3%), which are compounds commonly associated with anti‑inflammatory, antimicrobial, and tissue‑repair activities. Nanoencapsulation was achieved via chitosan‑assisted precipitation, and the resulting nanoparticles were characterized using Fourier transform infrared spectroscopy (FTIR), ultraviolet–visible (UV–Vis) spectroscopy, transmission electron microscopy (TEM), and X‑ray diffraction (XRD). FTIR spectra confirmed the successful incorporation of the extract within the chitosan matrix through the presence of characteristic O–H, N–H, and C=O functional groups without structural degradation. TEM analysis revealed predominantly spherical, mesoporous nanoparticles with particle sizes ranging from 2 to 50 nm and average diameters between 12.66 and 17.98 nm. UV–Vis spectroscopy demonstrated a hypsochromic shift in absorption maxima from 550 nm for the free extract to 375 nm for the nanoencapsulated formulation, indicating improved molecular dispersion and an encapsulation efficiency of 31.81%. XRD analysis revealed crystalline phases containing mineral oxides relevant to biological and pharmaceutical applications. Overall, the chitosan‑based nanoencapsulation of Imperata cylindrica root extract demonstrates significant potential as a natural product‑derived drug delivery system for topical wound‑healing and hemostatic applications, aligning with current advances in polymeric nanoparticle‑mediated drug delivery.